Antenatal fetal death in multiple pregnancy: is early prediction possible? - V. I. Tsibizova; D. V. Blinov; V. O. Bitsadze; T. M. Pervunina; E. V. Komlichenko; I. E. Govorov; E. K. Kudryashova; I. I. Averkin (IRBIS LLC, 2021)
Introduction. Perinatal mortality in multiple pregnancies increases by 8-10 times compared to singletons. Stillbirth is a significant part of all complications of multiple pregnancies. Although the incidence of perinatal mortality in multiple pregnancies has decreased consistently compared to extremely high rates in the past, it remains relatively high, despite significant positive changes in the management of such pregnancies. Aim: to assess the diagnostic potential of the first trimester's biochemical screening in multiple pregnancies for predicting antenatal fetal death. Materials and Methods. As part of a retrospective study, a cohort of twin pregnancies after in vitro fertilization (IVF), intracytoplasmic sperm injection (ICSI), or spontaneous conception underwent screening of the first trimester at 11+0-13+6 weeks of gestation as recommended by the Fetal Medicine Foundation. Determination of pregnancy-associated plasma protein-A (PAPP-A) in blood serum with subsequent calculation of the relative PAPP-A MoM (multiples of median) - a multiple of the median (an indicator of how much the individual test result deviates from the reference values) was performed. Results. Prenatal screening and outcomes of 302 multiple pregnancies showed that with PAPP-A MoM < 0.5, antenatal fetal death occurred with a frequency of 42.86 % (6/14), with PAPP-A MoM within the reference values - In 12.67 % (28/221), with PAPP-A MoM > 2.0 - in 6.7 % (2/30). Differences between patients with PAPP-A MoM < 0.5 and PAPP-A MoM within the reference values, as well as PAPP-A MoM < 0.5 and PAPP-A MoM > 2.0 were statistically significant (p = 0.002 and p = 0.004, respectively). No differences were detected between spontaneous and assisted reproductive technology (ART) pregnancies. Conclusion. In women with multiple pregnancies resulting from ART or spontaneous, PAPP-A MoM values below the reference interval (< 0.5) in the first trimester are associated with an increased risk of antenatal fetal death.